NUTM1-rearranged Carcinoma of the Thyroid: A Distinct Subset of NUT Carcinoma Characterized by Frequent NSD3-NUTM1 Fusions. (29th December 2022) - Barletta, Justine A.; Gilday, Steven D.; Afkhami, Michelle; Bell, Diana; Bocklage, Theresa; Boisselier, Pierre; Chau, Nicole G.; Cipriani, Nicole A.; Costes-Martineau, Valerie; Ghossein, Ronald A.; Hertzler, Hans J.; Kramer, Alan M.; et al.
Abstract : NUT carcinoma (NC) is a rare subtype of squamous cell carcinoma defined by NUTM1 rearrangements encoding NUT fusion oncoproteins (the most frequent fusion partner being BRD4 ) that carries a very poor prognosis, with most patients dying in under 1 year. Only rare primary thyroid NCs have been reported. Here, we evaluated a series of 14 cases. The median patient age at diagnosis was 38 years (range: 17 to 72 y). Eight of 13 cases with slides available for review (62%) showed a morphology typical of NC, whereas 5 (38%) had a non–NC-like morphology, some of which had areas of cribriform or fused follicular architecture resembling a follicular cell–derived thyroid carcinoma. For cases with immunohistochemistry results, 85% (11/13) were positive for NUT on biopsy or resection, though staining was significantly decreased on resection specimens due to fixation; 55% (6/11) were positive for PAX8, and 54% (7/13) for TTF-1. Tumors with a non–NC-like morphology were all positive for PAX8 and TTF-1. The fusion partner was known in 12 cases: 9 (75%) cases had a NSD3-NUTM1 fusion, and 3 (25%) had a BRD4-NUTM1 fusion. For our cohort, the 2-year overall survival (OS) was 69%, and the 5-year OS was 58%. Patients with NC-like tumors had a significantly worse OS compared with that of patients with tumors with a non–NC-like morphology ( P =0.0462). Our study shows that NC of the thyroid can mimic other thyroid primaries, has a high rate of NSD3 - NUTM1 fusions, and an overall more protracted clinical course compared with nonthyroid primary NC.